A New Swarm Intelligence Technique for Solving Economic Dispatch Problem - M. H., Sulaiman; Z. N., Zakaria; Muhammad Ikram, Mohd Rashid; S. R., Abdul Rahim (2013)

(untitled)
This paper presents a new swarm intelligence (SI) technique to solve economic dispatch (ED) problems in power system. As been acknowledge that ED is one of the most complex optimization problem to be performed in the planning and operation of a power system which is to determine the optimal generation scheduling so that the minimum cost can be obtained. In addition, the effect of equality and inequality constraints that embedded in this problem makes ED harder to solve by using conventional techniques. In this paper, a recent SI technique,namely differential search (DS) algorithm is implemented to solve ED problem. DS simulates the Brownian-like random-walk movement used by organisms to migrate. In order to demonstrate the effectiveness of DS, two test systems viz. 15-units system and TAIPOWER 40-units system are utilized as test cases and compared to the other technique.instructions give you basic guidelines for preparing papers for conference proceedings.